Dabrafenib plus trametinib in patients with relapsed/refractory BRAF V600E mutation-positive hairy cell leukemia - Kreitman, Robert; Moreau, Philippe; Ravandi, Farhad; Hutchings, Martin; Gazzah, Anas; Michallet, Anne-Sophie; Wainberg, Zev A.; Stein, Alexander; Dietrich, Sascha; de Jonge, Maja J. A.; Willenbacher, Wolfgang; De Grève, Jacques; et al. (Blood, 2023)
BRAF V600E is the key oncogenic driver mutation in hairy cell leukemia (HCL). We report the efficacy and safety of dabrafenib plus trametinib in patients with relapsed/refractory BRAF V600E mutation-positive HCL. This open-label, phase 2 study enrolled patients with BRAF V600E mutation-positive HCL refractory to first-line treatment with a purine analog or relapsed after ≥2 prior lines of treatment. Patients received dabrafenib 150 mg twice daily plus trametinib 2 mg once daily until disease progression, unacceptable toxicity, or death. The primary endpoint was investigator-assessed objective response rate (ORR) per criteria adapted from National Comprehensive Cancer Network-Consensus Resolution guidelines. Secondary endpoints included duration of response (DOR), progression-free survival (PFS), overall survival (OS), and safety. Fifty-five patients with BRAF V600E mutation-positive HCL were enrolled. The investigator-assessed ORR was 89.0% (95% confidence interval, 77.8%-95.9%); 65.5% of patients had a complete response (without minimal residual disease [MRD]: 9.1% [negative immunohistochemistry of bone marrow BM biopsy], 12.7% [negative BM aspirate flow cytometry FC], 16.4% [negative immunohistochemistry and/or FC results]; with MRD, 49.1%), and 23.6% had a partial response. The 24-month DOR was 97.7% with 24-month PFS and OS rates of 94.4% and 94.5%, respectively. The most common treatment-related adverse events were pyrexia (58.2%), chills (47.3%), and hyperglycemia (40.0%). Dabrafenib plus trametinib demonstrated durable responses with a manageable safety profile consistent with previous observations in other indications and should be considered as a rituximab-free therapeutic option for patients with relapsed/refractory BRAF V600E mutation-positive HCL. This trial is registered at www.clinicaltrials.gov as #NCT02034110.
Gesehen am 07.06.2023